Analisis Pengelolaan SDM, Manajemen Keuangan, Teknologi Dan Inovasi Sebagai Strategi Keberlangsungan Hidup Home Industry Bakso Malang - Gunawan Aji; Nova Karisma; Fitriyani Fitriyani; Serlinda Ane Yulaicha; Alfina Dita Damayanti (International Forum of Researchers and Lecturers, 2023)
Home industry is a business unit on a small scale engaged in certain industrial fields. Even thought it is a small business unit, a development strategy is needed so that the business can run well and survive amidst the motivations of other businesses. The innovation needs to be supported by good financial management so that the innovations created by home industry owners can be realized. It is necessary to have human resources who are literate about today’s technology. This technology is not only used for marketing but also a means to seek various innovations business product.